Albumin Levels before Therapy and Clinicopathological Parameters of Lung Cancer Patients - Erna Kusumawardhani; Nor Fiayanti Hadiani (Universitas Airlangga, Surabaya, Indonesia, 2025)
Highlights A notable finding was the significant relationship between albumin levels and ECOG scores, emphasizing the potential of albumin as an indicator of functional status in lung cancer patients. The research provided a comprehensive analysis of the correlation between albumin levels and various clinicopathological conditions. Background: Serum albumin levels provide an objective measure of malnutrition. Albumin plays crucial roles in maintaining intravascular oncotic pressure, facilitating substance transport, and acting as a free radical scavenger. The progression of tumors, including lung cancer, is closely associated with malnutrition and cancer-related inflammation, which suppress albumin synthesis. Therefore, albumin can serve as a biomarker for assessing lung cancer progression. Low albumin levels are linked to poor prognosis. Objective: The aim of this study was to examine the relationship between albumin levels and lung cancer. Material and Method: This study included 130 lung cancer patients who underwent albumin testing. A cross-sectional study was conducted using medical records of patients diagnosed with lung cancer from January 2023 to December 2023. Data were collected on various factors, including age, gender, smoking status, cancer history, clinical symptoms, histopathological type, cancer stage, EGFR mutation status, ECOG score, clinical pleural effusion, Visual Analog Scale (VAS), and Body Mass Index (BMI). Result: The study sample was predominantly male (71.5%), aged over 50 years (76.9%), and active smokers (34.6%). Common symptoms included cough (83.8%) and shortness of breath (72.3%), with pleural effusion present in 53.8%. The majority had a moderate VAS score (46.9%) and were classified as underweight based on BMI (54.6%). Most patients were at stage IVA (63.0%), had an ECOG score of 1 (43.8%), and were diagnosed with adenocarcinoma (73.8%). A significant relationship was found between ECOG scores and albumin levels, with 70.6% of hypoalbuminemic samples having an ECOG score of 3 (p < 0.005). Conclusion: A significant relationship was observed between albumin levels and ECOG scores in lung cancer patients.